Factors Affecting the Adoption of Artificial Intelligence Voice Control Technology: A Case Study of Xiaomi Smart Devices - Punyanut Traiyatha; Jiroj Buranasiri (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
The research aims to examine the factors influencing the adoption of artificial intelligence voice control technology. The purposive sampling technique was applied to collect the sample of 400 people who had experience in using Xiaomi smart device. The online questionnaire is the instrument for data collection. Descriptive statistics are used to analyze the respondents’ characteristic. The inferential statistics include Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) are applied to disclose the impact of utilitarian benefits, hedonic benefits, symbolic benefits, social presence, and social attraction on the adoption of artificial intelligence voice control technology. The results of this research can be used to improve the voice command technology for future users. Additionally, the study’s report can be used for developing voice control systems in smart devices for other business enterprises. Subsequently, the users’ concern about the risk of using voice commands would subside and this technology would be widely accepted.